Derivation of Structural Checklist for Safety Evaluation of Apartment Remodeling - Kyungbum, Kim; Daiyoung, Yune; Taeho, Kim; Jinyoung, Kim (Journal of the Architectural Institute of Korea, 2022)
The market size of domestic apartment remodeling continues to grow; however, thus far only a single case has passed vertical expansion remodeling. For safety purposes, the Ministry of Land, Infrastructure, and Transport established and announced safety review standards for vertical expansion remodeling. There were many cases where standards were not properly comprehended leading to the omission of essential safety evaluation documents. Consequently, it took more time than expected to conduct the review process that resulted in project delays and an increase in expenses. For these reasons, relevant practitioners need to be fully acquainted with the safety evaluation and structural manuals while evaluation documents should be reviewed thoroughly before submission. The purpose of this study is to derive a practical structural checklist, especially for vertical expansion remodeling, to improve the efficiency of remodeling projects and structural safety. To derive a checklist, the safety reviews and deliberation cases of nine complexes, a total of 606 deliberation opinions, were collected. Based on these, a structural checklist was derived with 44 items. It is expected that this derived structural checklist will be used to review safety evaluation documents to reduce the time required for stakeholders including unions, practitioners, and institutions.
Keywords: Apartment house; Remodeling; Structural Checklist, Safety Evaluation